Frequency of Carpal Tunnel Syndrome and Related Functional Status in Computer Operators - Samreen Yasmeen, Farhan Ishaque, Syeda Maliha Ali, Saleha Irshad, Ummul Qura, Tasfia Syed, Samreen Yasmeen, Farhan Ishaque, Syeda Maliha Ali, Saleha Irshad, Ummul Qura, Tasfia Syed (Journal of Rawalpindi Medical College, 2022)
Objective: To find out the frequency of Carpal Tunnel Syndrome (CTS) and associated functional limitations in computer operators. Materials &Methods: This cross-sectional study was conducted in the premises of DUHS, Ojha campus, Karachi. The duration of study is from 1st Dec 2019 to 29th February 2020.Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) was used to evaluate the frequency of CTS in computer users, total sample size taken was 95, data was collected in the premises of DUHS, Ojha campus including both males and females employs between age group of 25 to 50 years that were working on the current job for more than 2 years, members that were <25 or >50 years were excluded from the study. Results: The study indicated possible association of Symptom severity and functional limitations with respect to age. The frequency of CTS symptoms with moderate to severe severity was 17.9% and 35.8% respectively whereas 46.3% reported mild symptoms. According to functional status scale 55.8% had mild functional limitations whereas moderate to severe difficulty in performing day to day activities was found 21.1% and 23.0% respectively. Conclusion: This study survey indicated that computer using is associated with the development of CTS symptoms. It also results in the increasing the severity of the symptoms, causing prominent functional limitations that interferes with proper working of employs. Keywords: carpal tunnel syndrome, frequency, computer users, functional limitations.